Perceptions of Saudi women in Malaysia on gender equality in the Kingdom of Saudi Arabia - Asirri, Turkyah Abdurahman (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2019)
For a considerable length of time, Western media, researchers, and activists, have examined the gender equality in the Kingdom of Saudi Arabia. There are many misconceptions on whether Islam plays a significant role in the gender equality between men and women. This research shows that Western media, researchers, and activists discussions are based on material collected from sources lacking reliable information about Saudi Arabia. Women in Saudi Arabia, like women in any country, have their perception of equality. They play a pre-eminent role not only within their families but also outside as well. Development in Saudi Arabia has provided increasing opportunities for women in education, employment and political participation. This study aims to examine and analyse the perceptions of Saudi women in Malaysia on gender equality in Saudi Arabia. To achieve the objectives of the current study, the quantitative method was adopted. The survey included 140 respondents from Saudi women living in Malaysia by using a random sampling technique. Statistical Package processed data for Social Sciences (SPSS) IBM version 24 was used to analyzed the data with the use of descriptive statistics for analysis presentation. The study recommended that the Saudi government should ensure an equal share of female employees versus male employees in all sectors in Saudi Arabia. There is also a need to improve the benefits of working mothers. Strengthen the right of Saudi women to choose the type of education and participate in the labour market. The findings from this study can be used as a benchmark for the improvement of gender equality in the Kingdom of Saudi Arabia.